Perlindungan Hukum Terhadap Anak Korban Kekerasan Seksual - Mastur Mastur; Syamsuddin Pasamai; Abdul Agis (Journal of Lex Philosophy (JLP), 2020)
Penelitian bertujuan untuk menganalisis perlindungan hukum terhadap anak korban kekerasan seksual, dan menganalisis faktor yang mempengaruhi perlindungan hukum terhadap anak korban kekerasan seksual. Tipe penelitian ini adalah yuridis empiris. Hasil Penelitian bahwa; Perlindungan hukum terhadap anak yang menjadi korban kekerasan seksual dalam praktik penegakan hukum pidana oleh Kepolisian di Polewali Mandar adalah perlindungan dalam proses penyelidikan serta melalui upaya preventif/pencegahan dengan bekerja sama dengan Lembaga Swadaya Masyarakat (LSM) di Kabupaten Polewali. Sedangkan perlindungan hukum oleh Pengadilan Negeri Polewali adalah perlindungan dalam proses persidangan yang berupa korban anak tidak disumpah, hakim dalam memberikan pertanyaan sangat hati-hati dan tidak formal, serta adanya pendamping yang dipercaya oleh korban anak. Perlindungan hukum terhadap anak korban kekerasan seksual tidak berjalan secara efektif dikarenakan masih terdapat tindak kekerasan seksual anak yang pada kenyataannya saat ini masih banyak yang menimpa anak di Kabupaten Polewali Mandar. This study aims to analyze the legal protection of child victims of sexual violence, and to analyze the factors that influence the legal protection of child victims of sexual violence. This type of research is juridical empirical. Research results that; Legal protection for children who are victims of sexual violence in criminal law enforcement practices by the Police in Polewali Mandar is protection in the investigation process and through preventive / preventive measures in collaboration with Non-Governmental Organizations (NGOs) in Polewali Regency. Meanwhile, legal protection by the Polewali District Court is protection in the trial process in the form of child victims who are not sworn in, judges in giving questions are very careful and informal, and there is a companion who is trusted by child victims. Legal protection for child victims of sexual violence does not work effectively because there are still acts of child sexual violence which in fact currently still happen to many children in Polewali Mandar Regency. the factors that influence the legal protection of child victims of sexual violence. This type of research is juridical empirical. Research results that; Legal protection for children who are victims of sexual violence in criminal law enforcement practices by the Police in Polewali Mandar is protection in the investigation process and through preventive / preventive measures in collaboration with Non-Governmental Organizations (NGOs) in Polewali Regency. Meanwhile, legal protection by the Polewali District Court is protection in the trial process in the form of child victims who are not sworn in, judges in giving questions are very careful and informal, and there is a companion who is trusted by child victims. Legal protection for child victims of sexual violence does not work effectively because there are still acts of child sexual violence which in fact currently still happen to many children in Polewali Mandar Regency